Photoexcited Palladium Complex-Catalyzed Isocyanide Insertion into Inactivated Alkyl Iodides - Andrea Messina; Filippo Monticelli; Tiziano Miroglio; Anna Gagliardi; Igor Viviani; Luca Banfi; Renata Riva; Lisa Moni; Andrea Basso; Chiara Lambruschini (Molecules)
Isocyanides insertions represent an important transformation in the palladium-catalyzed reactions landscape. However, one of their most significant limitations is in the use of inactivated alkyl electrophiles. Palladium photocatalysis has been proven as a solid tool for the generation of alkyl radicals from alkyl halides, which may engage in subsequent transformations with a variety of reaction partners, closing the catalytic cycle. Herein, we report the mild three-component isocyanide insertions into inactivated alkyl iodides mediated by the catalytic activity of a photoexcited palladium complex. We investigated the scope of the reaction obtaining differently substituted secondary amides in good to high yields. We also investigated the mechanism, hypothesizing a key role of 4-(N,N-dimethylamino)pyridine in the outcome of the reaction.